CULTURE-BASED CHARACTER EDUCATION IN MODERNITY ERA - Muhammad Murtako (Ta'dib: Jurnal Pendidikan Islam, 2015)
Education cannot be separated from culture. It is a product of human culture and becomes part of the culture. It also seeks to transform the cultural values in order to achieve both individual and community progress. The implementation of culture-based character education highlights the importance of exemplary elements.